Development of AI-based Arabic Learning Model to Improve non-native speaker Arabic Speaking Skills - M Syaikhudin; M Isroul Laili (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
This research delves into the development of an Artificial Intelligence (AI)-based Arabic language learning model with the aim of enhancing Arabic speaking skills for non-native speakers. The background of this research arises from the complexity of Arabic language learning, which requires not only an understanding of grammar and vocabulary but also proficiency in speaking with an accurate accent and intonation. The research methodology includes the selection of suitable AI algorithms, the development of a prototype model, and further testing on non-native speakers at the Sekolah Tinggi Agama Islam (STAI) al-Yasini, Pasuruan. The utilization of AI technology is expected to provide innovative solutions to address individual learning needs in the context of the Arabic language. Mid-term evaluation results indicate that the AI learning model can positively impact Arabic speaking skills, although improvements are still necessary. User response analysis provides valuable insights that serve as the basis for further model refinements. Suggestions for future research include further development of the AI model, broader testing across various non-native speaker groups, and the integration of user feedback to enhance Arabic speaking skills holistically. The implications of these research findings are expected to significantly contribute to the development of adaptive and innovative Arabic language learning.